Chinese paintings : tradition and innovation in 20th century Chinese painting / On collecting Chinese paintings of the 20th century - http://id.worldcat.org/fast/1984986; http://id.worldcat.org/fast/161442 (Art Gallery of Greater Victoria, 1998)
Catalogue of an exhibition of modern Chinese paintings. Includes bibliographical references and index. Designed and printed in Canada by Morriss Printing Company Ltd. Victoria British Columbia.